2017
DOI: 10.1177/2048872617690887
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion ventricular arrhythmia bursts identify larger infarct size in spite of optimal epicardial and microvascular reperfusion using cardiac magnetic resonance imaging

Abstract: In the presence of suboptimal reperfusion with MVO by CMR, VA burst does not further define MI size. However, with optimal TIMI 3 reperfusion and optimal microvascular perfusion (i.e. no MVO), VA burst is associated with larger IS, indicating that VA burst is a marker of additional cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The same pathophysiology that exists in IR injury, e.g., apoptosis and mitochondrial dysfunction, drives many forms of arrhythmias, including the main type, accelerated idioventricular rhythms [47]. Thus, the two conditions complement each other and, together, contribute to larger infarct size, meaning more myocyte death and decreased ventricular functioning [47][48][49][50][51][52][53]. Notably, studies support that reperfusion without arrhythmia has a smaller infarct size regardless of the same initial areas at risk [47][48][49][50][51][52].…”
Section: Role Of Cardiac Mir-1 In Ir Injurymentioning
confidence: 99%
“…The same pathophysiology that exists in IR injury, e.g., apoptosis and mitochondrial dysfunction, drives many forms of arrhythmias, including the main type, accelerated idioventricular rhythms [47]. Thus, the two conditions complement each other and, together, contribute to larger infarct size, meaning more myocyte death and decreased ventricular functioning [47][48][49][50][51][52][53]. Notably, studies support that reperfusion without arrhythmia has a smaller infarct size regardless of the same initial areas at risk [47][48][49][50][51][52].…”
Section: Role Of Cardiac Mir-1 In Ir Injurymentioning
confidence: 99%
“…This connection is supported by previous findings by our group. [3][4][5][6][7][8][9] We found, in several independent cohorts, the presence of a 'burst' of ventricular reperfusion arrhythmias (VA burst) to be related to clinically significant larger infarct size. This increase remained while correcting for other known factors of increased infarct size.…”
Section: Correlation Between Fatal Reperfusion Injury and Reperfusionmentioning
confidence: 94%
“…reopening of the infarct vessel, more recent studies have shown that reperfusion without arrhythmias resulted in smaller infarcts in spite of equal initial areas at risk. [3][4][5][6][7][8]…”
Section: Reperfusion Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a study of STEMI patients in whom infarct size and microvascular obstruction was assessed by cardiac magnetic resonance imaging a burst of reperfusion ventricular arrhythmias was associated with a much greater infarct size. 13 The increased infarct size was only observed in the group of patients with an optimal TIMI 3 epicardial blood flow and no microvascular obstruction. It appears therefore that a burst of reperfusion ventricular arrhythmias is an independent marker of additional myocardial reperfusion injury.…”
mentioning
confidence: 94%